What Are the Long-term Results of MUTARS(®) Modular Endoprostheses for Reconstruction of Tumor Resection of the Distal Femur and Proximal Tibia? - Bus, Michaël P. A. (Clin Orthop Relat Res, 2015)
BACKGROUND: Modular endoprostheses are commonly used to reconstruct defects of the distal femur and proximal tibia after bone tumor resection. Because limb salvage surgery for bone sarcomas is relatively new, becoming more frequently used since the 1980s, studies focusing on the long-term results of such prostheses in treatment of primary tumors are scarce. QUESTIONS/PURPOSES: (1) What proportion of patients experience a mechanical complication with the MUTARS(®) modular endoprosthesis when used for tumor reconstruction around the knee, and what factors may be associated with mechanical failure? (2) What are the nonmechanical complications? (3) What are the implant failure rates at 5, 10, and 15 years? (4) How often is limb salvage achieved using this prosthesis? METHODS: Between 1995 and 2010, endoprostheses were the preferred method of reconstruction after resection of the knee in adolescents and adults in our centers. During that period, we performed 114 MUTARS(®) knee replacements in 105 patients; no other endoprosthetic systems were used. Four patients (four of 105 [4%]) were lost to followup, leaving 110 reconstructions in 101 patients for review. The reverse Kaplan-Meier method was used to calculate median followup, which was equal to 8.9 years (95% confidence interval [CI], 8.0–9.7). Mean age at surgery was 36 years (range, 13–82 years). Predominant diagnoses were osteosarcoma (n = 56 [55%]), leiomyosarcoma of bone (n = 10 [10%]), and chondrosarcoma (n = 9 [9%]). In the early period of our study, we routinely used uncemented uncoated implants for primary reconstructions. Later, hydroxyapatite (HA)-coated implants were the standard. Eighty-nine reconstructions (89 of 110 [81%]) were distal femoral replacements (78 uncemented [78 of 89 {88%}, 42 of which were HA-coated [42 of 78 {54%}]) and 21 (21 of 110 [19%]) were proximal tibial replacements. In 26 reconstructions (26 of 110 [24%]), the reconstruction was performed for a failed previous reconstruction. We used a competing risk model to estimate the cumulative incidence of implant failure. RESULTS: Complications of soft tissue or instability occurred in seven reconstructions (seven of 110 [6%]). With the numbers we had, for uncemented distal femoral replacements, we could not detect a difference in loosening between revision (five of 17 [29%]) and primary reconstructions (eight of 61 [13%]) (hazard ratio [HR], 1.72; 95% CI, 0.55–5.38; p = 0.354). Hydroxyapatite-coated uncemented implants had a lower risk of loosening (two of 42 [5%]) than uncoated uncemented implants (11 of 36 [31%]) (HR, 0.23; 95% CI, 0.05–1.06; p = 0.060). Structural complications occurred in 15 reconstructions (15 of 110 [14%]). Infections occurred in 14 reconstructions (14 of 110 [13%]). Ten patients had a local recurrence (10 of 101 [10%]). With failure for mechanical reasons as the endpoint, the cumulative incidences of implant failure at 5, 10, and 15 years were 16.9% (95% CI, 9.6–24.2), 20.7% (95% CI, 12.5–28.8%), and 37.9% (95% CI, 16.1–59.7), respectively. We were able to salvage some of the failures so that at followup, 90 patients (90 of 101 [89%]) had a MUTARS(®) in situ. CONCLUSIONS: Although no system has yet proved ideal to restore normal function and demonstrate long-term retention of the implant, MUTARS(®) modular endoprostheses represent a reliable long-term option for knee replacement after tumor resection, which seems to be comparable to other modular implants available to surgeons. Although the number of patients is relatively small, we could demonstrate that with this prosthesis, an uncemented HA-coated implant is useful in achieving durable fixation. LEVEL OF EVIDENCE: Level IV, therapeutic study.